Design and Performance Analysis of Compliant Actuator Mechanism with Variable Stiffness - Liu Rong; Zheng Zhizhen; Qin Huibin; Li Zhongyi; Bai Shaoping (Jixie chuandong)
Controllable variable stiffness compliant actuator mechanism has the characteristics of high compliance, high environmental adaptability and good man-machine interaction. The variable stiffness compliant actuator mechanism is based on the transmission principle of a four-bar linkage with a zero-length rack. The variable stiffness control can be realized by changing the properties and the winding mode of the elastomer, or the configuration scheme. Through configuration analysis and structure design, the stiffness and torque models of the compliant actuator mechanism are established to reveal its stiffness behavior. The Lagrangian method is used to establish the dynamic model of the compliant actuator mechanism, and the frequency theoretical results are obtained by solving the average stiffness. The virtual prototype is established to motion simulation, which reveals its performance characteristics and verifies the correctness of theoretical analysis. Compared with other similar designs, the compliant actuator mechanism proposed has the characteristics of miniaturization and lightweight with strong applicability. It can be used as a single module and integrated into the exoskeleton system.